Reevaluating the crucial contributions of pharmacy technicians: A comprehensive review - Alharbi, Khalid Saud (International journal of economic perspectives, 2014)
Community-based processes can dissuade pharmacy technicians' professional development and self-motivation. Many of the challenges outlined earlier can have an implicit disincentive effect on interest in the benefits of further professional development or interest in transitioning into a new potential role such as the CPhT. There are, however, opportunities on the horizon. The first part of this report—the consolidated research literature—accounts for the many clinical or distributive tasks that pharmacy technicians are capable of performing, whether in hospital, ambulatory care, or community-based teams at top-of-license level. The need for continuation of education or lifelong learning was a common theme emerging from the literature. In practice, advancement through a hybrid career ladder that is sensitive to the ability to practice competently has been linked to mentorship and preceptorship in a controlled hospital practice-based research network.